Impact of Green Economy and Innovation on Sustainable Development With Regulatory Quality Mediation: Indonesia Case - Elmira Siska; Rini Larasati Irawan; Tri Lestari; Dorris Yadewani (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Green economy and innovation are key drivers of sustainable development; however, their effectiveness depends on the regulatory quality that governs their implementation. In Indonesia, regulatory challenges often hinder efforts to promote a green economy and innovation, raising concerns about their direct and mediated impact on sustainable development.Purpose: To examine how the green economy and innovation affect sustainable development in Indonesia, using regulatory quality as a mediating variable.Design/methodology/approach: This study used a quantitative technique with annual time-series data from 2011 to 2020. The variables analyzed included Green Economy (X1), innovation (X2), Regulatory Quality (Z), and Sustainable Development (Y). Data analysis was performed using OLS regression, starting with classical assumption tests followed by hypothesis testing. The data were processed using EViews-12.Findings/Result: The findings prove that the green economy does not significantly impact regulatory quality, while innovation negatively impacts it. However, a green economy directly enhances sustainable development, whereas innovation does not. Regulatory quality significantly influences sustainable development and mediates the effects of both the green economy and innovation.Conclusion: This study underscores the importance of regulatory quality in enhancing green economic policies and mitigating the negative effects of innovation. Strengthening regulatory frameworks is necessary to optimize the benefits of green economic endeavors and foster sustainable innovation. Originality/value (State of the art): This research adds value by highlighting the mediating role of regulatory quality, offering a more comprehensive perspective on sustainability governance in Indonesia. Keywords:  economy policies, green economy, innovation, regulatory quality, sustainable development